Benznidazole affects expression of Th1, Th17 and Treg cytokines during acute experimental Trypanosoma cruzi infection - Mariana Gatto; Larissa Ragozo Cardoso Oliveira; Fernanda De Nuzzi Dias; João Pessoa Araújo Júnior; Carlos Roberto Gonçalves Lima; Eliana Peresi Lordelo; Rodrigo Mattos dos Santos; Cilmery Suemi Kurokawa (Journal of Venomous Animals and Toxins including Tropical Diseases, 2017)
Abstract Background The present study evaluated the effect of treatment with benznidazole on mRNA expression of IFN-γ, IL-17, IL-10, TGF-β and FoxP3 in spleen and heart tissue of BALB/c mice in the acute phase of an experimental infection with Trypanosoma cruzi, strains JLP or Y. Methods The mRNA expression of cytokines and parasite load were assessed by q-PCR. Dependent groups were compared using Student’s paired t-test and independent groups were compared using Student’s unpaired t-test. Results Infection with the JLP or Y strains increased expression of IFN-γ in the heart and of IL-10 and IL-17 in the spleen and heart compared to uninfected animals. Treatment increased the expression of IFN-γ and decreased the expression of IL-17, IL-10, TGF- β and Foxp3 in spleen and heart tissue compared to untreated infected animals. Conclusion Benznidazole can induce Th1 profile in the initial of the acute phase. The treatment decreased the parasite load in both organs, although the number of parasites in Y-strain-infected mice remained high. The data suggest that benznidazole may modulate cytokine expression in infection and can be dependent of the strain. However, treatment was not fully effective in the infection provoked by Y strain, probably due to the characteristics of the strain itself.